Forming Electro - Mechanical Transparent (Polymer -Ni) Sensor - AL.Bedin, S. A.; ALHamed, A .A .; AL.Sarraf, A. R.; Dambus, H.I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Polymers (Silicon elastomer) are used lately as a conductive material in electronic application in addition to be transparent, to light. In this paper we prepared polymer films about (1mm) thick and less which contain Ni-metal powder cured in magnetic vacuum furnaces at temperature 120Â°C in order to arrange or to be oriented the particles of the Ni- powder through the polymer in such a way to be conductive for electric currents. We found that these films are sensitive to any loads on the surface (force per unit area). Using light loads on a unit electric cell from these films, we get an electric transparent sensor that could be used in sensing applications.